ALIF versus TLIF for Post-Discectomy Syndrome - Jägersberg, Max; Schneider, Kristian; Schaller, Carlo; Richter, Marcus (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Objective To evaluate whether anterior lumbar interbody fusion (ALIF) is superior to transforaminal lumbar interbody fusion (TLIF) in cases of post-discectomy syndrome (PDS).Methods In this retrospective study, we analyzed the consecutive results of 83 patients operated for PDS refractory to conservative treatment. A total of 46 patients underwent ALIF via a retroperitoneal approach; 37 patients underwent TLIF. Both fusion types were augmented by means of pedicle screw instrumentation. Early and delayed complications were registered within the course of hospitalization or outpatient clinical follow-up, respectively. Parameters such as patient satisfaction, current pain levels, pain medication, and change in work ability were obtained via telephone follow-up.Results Overall, 81.9% of patients were available for follow-up. Both ALIF and TLIF significantly improved back and leg pain (p < 0.01) and were described as satisfying operations by 75.8% and 73.3% of the patients, respectively. No significant difference between ALIF and TLIF results could be observed. Complications included dural tears, screw malposition, bleeding from major vessels (ALIF), abdominal wall insufficiency (ALIF), and nerve root injury (TLIF). One patient in the ALIF group and seven patients in the TLIF group required fusion extensions to adjacent levels within the observation period (observation period was 34 and 71 months, respectively).Conclusions Both ALIF and TLIF techniques can be applied for PDS with equally good results. The technical advantages of ALIF have to be balanced with the additional morbidity and operation time owed to the additional approach. ALIF might be associated with a lower incidence of adjacent level disease compared with TLIF.
Keywords: post-discectomy syndrome; ALIF; TLIF